Impact of climate-induced water-table drawdown on carbon and nitrogen sequestration in a Kobresia-dominated peatland on the central Qinghai-Tibetan Plateau - Tingwan Yang; Jingjing Sun; Yuefeng Li; Meng Wang; Hongkai Li; Shengzhong Wang; Zhengyu Xia; Zicheng Yu (Communications Earth & Environment)
Abstract Peatlands on the Qinghai-Tibetan Plateau (QTP) represent one of the world’s largest reservoirs of soil organic carbon (C) and nitrogen (N), but their future stability is uncertain. This study utilizes high-resolution multi-core records of C and N contents, stable isotopes, and infrared spectroscopy to reconstruct water table depths and their impacts on C and N accumulation and decomposition over the past 2.7 kyr in a slope peatland from the central QTP. Our paleo records reveal that increased decomposition in the surface oxic layer has led to decreased C and N accumulation rates over the last millennium, primarily due to water-table drawdown driven by climate warming and drying. Supporting evidence from nearby records suggests that this trend of surface drying may be widespread across QTP peatlands. Despite this, QTP peatlands retain some of the highest 1-m C and N densities globally, with values of 54.1 ± 18.9 kg C m-2 and 3.2 ± 1.5 kg N m-2. These findings highlight the vulnerability of substantial C and N reservoirs and sequestration capabilities in QTP peatlands to continued water table declines in a warming and drying climate.